2015
DOI: 10.1021/acs.orglett.5b01128
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Addition-Type Alkenylation of Unactivated, Aliphatic C–H Bonds with Alkynes: A Concise Route to Polysubstituted γ-Butyrolactones

Abstract: Through the nickel-catalyzed chelation-assisted C-H bond activation strategy, the addition-type alkenylation of unreactive β-C(sp(3))-H bonds of aliphatic amides with internal alkynes is developed for the first time to produce γ,δ-unsaturated carboxylic amide derivatives. The resulting alkenylated products can further be transformed into polysubstituted γ-butyrolactones with pyridinium chlorochromate (PCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…The product 2a was obtained in 86 % isolated yield under the optimized reaction conditions: [NiBr 2 (dme)]( 10 mol %) as the catalyst,S IMes·HCl (20 mol %) as the ligand,K O tBu (22 mol %) as the base for the in situ generation of the NHC ligand with 5equiv of diphenylacetylene in The base, KOtBu plays an important role for the efficiency of the reaction,s uch as not only for the generation of the NHC ligand,b ut also to accelerate the reaction.A n alkenylation product 3 was not obtained in all cases. [21] It was found that the use of an 8-aminoquinoline as the directing group was essential for the success of the reaction, while other directing groups, which are known to promote CÀ Hb ond activation reactions, did not afford the desired products (Scheme 3and Table S3 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The product 2a was obtained in 86 % isolated yield under the optimized reaction conditions: [NiBr 2 (dme)]( 10 mol %) as the catalyst,S IMes·HCl (20 mol %) as the ligand,K O tBu (22 mol %) as the base for the in situ generation of the NHC ligand with 5equiv of diphenylacetylene in The base, KOtBu plays an important role for the efficiency of the reaction,s uch as not only for the generation of the NHC ligand,b ut also to accelerate the reaction.A n alkenylation product 3 was not obtained in all cases. [21] It was found that the use of an 8-aminoquinoline as the directing group was essential for the success of the reaction, while other directing groups, which are known to promote CÀ Hb ond activation reactions, did not afford the desired products (Scheme 3and Table S3 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The use of 2equiv of diphenyacetylene and 0.5 equiv of pivalic acid in a2hreaction did not give 2a,b ut instead the alkenylation product 3 was obtained in 47 %i solated yield, with the starting material 1a being recovered( 34 %; Scheme 5). [21] We next examined the use of dialkylalkynes as the coupling partner because such alkyl chains could increaset he solubility and stability of polyarenes in organic solvents, which is an importanti ssue forp otentiala pplications. [26] The reaction of 1a with 4-octyne and 8-hexadecyne afforded good yields (4a 60 %, and 4b 45 %), alongw ith small amountso fortho-alkenylated products 5a (7 %) and 5b (trace;Scheme 6).…”
Section: Resultsmentioning
confidence: 99%
“…Internal alkynes turned out to be suitable coupling partners in the alkenylation of aliphatic chains under Ni-catalysis as demonstrated by the methodologies developed by You ( Scheme 81B ) 486 and Maiti ( Scheme 81C ). 487 Zhang used terminal alkynes ( Scheme 81D ).…”
Section: Bidentate Dgsmentioning
confidence: 99%
“…Further synthetic transformation was illustrated by treating 3 f with 3‐chloroperoxybenzoic acid ( m ‐CPBA) and NaHCO 3 (Scheme ). The polycyclic lactone (±)‐ 5 was afforded in 71 % yield …”
Section: Methodsmentioning
confidence: 99%